DEVELOPMENT OF SCIENCE AND TECHNOLOGY IN THE PAI CURRICULUM - Nasir, Tatang Muh; Hasbiyallah, Hasbiyallah; Syarif, Ahmad (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
Education is a conscious effort to prepare students through guidance, teaching and/or training activities, as well as equipping students with knowledge for their future roles. Meanwhile, technology is the application of scientific knowledge and other sciences to solve practical problems. Thus science and technology cannot be separated. Science and technology are developing very rapidly along with the pace of development of society. Science and technology have a reciprocal relationship with education and the curriculum. Education and curriculum must be able to respond to the rapid development of science and technology, because education is an effort to prepare students to face a better future. Curriculum development for all subjects including Fiqh must be based on developments in science and technology. The development of science and technology directly has implications for curriculum development which includes objectives, materials, methods and evaluation. Technology has an important role in developing the Fiqh curriculum because Fiqh material must always be up to date with the conditions and needs of students. Fiqh learning must always be contextual to students' real lives so that its existence is always present and becomes a student's need.